On the green side of trade competitiveness? Environmental policies and innovation in the EU - Valeria Costantini; Massimiliano Mazzanti (Fondazione Eni Enrico Mattei (FEEM), 2010)
This paper aims to explore how the competitiveness of the EU economy, here captured by export dynamics over the medium run (1996-2007), has been affected by environmental regulation both on the public and private sector side. The strong and weak versions of the Porter hypothesis are tested by specifying the export dynamics of five aggregated manufacturing sectors classified by their technological or environmental content using a dynamic panel data estimator applied to a theoretically-based gravity model. When testing the strong version on export performances of manufacturing sectors, the overall effect of environmental policies does not conflict with export competitiveness. When testing the weak version using export flows of environmental goods, environmental policies, as well as innovation activities, all foster competitive advantages of green exports. Public policies and private innovation patterns trigger higher efficiency in the production process, thus turning the perception of environmental protection actions as a production cost into a net benefit. These results constitute useful advice for policy makers involved in the new wave of environmental tax reforms and green recovery packages currently debated at European Union level.
Keywords: F14; O14; Q43; Q56; 330; Environmental Policies; Porter Hypothesis; Technological Innovation; Export Performances; Gravity Model; European Union